“THE CITY RUSHES TO RENOVATE”. PLAZA DE LA CULTURA, SAN JOSÉ, COSTA RICA (1969-1982) - Brenes Rodríguez, Milton Ariel (2023)
This article analyzes the interests and political and cultural disputes surrounding the construction of the Plaza de la Cultura in San Jose, Costa Rica between 1969 and 1982. The study is guided by Michel Foucault’s genealogical strategy and post-structuralist social theory. This article makes use of newspapers, government documents, audiovisuals, and photographs of the Plaza de la Cultura. This article examines the design of this urban works project as part of a broader commitment by this nation’s dominant social democratic party, Liberación Nacional, to modernize the capital city of San Jose, between 1970 and 1978 as part of this party’s Entrepreneurial State political program. Secondarily, this article asserts between 1970 and 1982, the construction and inauguration of the Plaza was used by Liberación Nacional’s political opponents, namely members of the Partido Coalición Unidad political party, to critique the ruling party, This article reveals how both the 1980 financial crisis and the critiques by the Partido Coalición Unidad served to check Liberación Nacional’s entrepreneurial state program.